Challenges of Smart Cities: Methods of Prioritization - Omar Atef Orabi; Ahmed Morsi Galil (International Journal of Computers and Informatics, 2023)
Smart city development has gotten considerable recognition in systematic literature and international policies throughout the world. The study aims to identify the key barriers to smart cities from the review of existing literature and the views of experts in this area. This work further made an attempt on the prioritization of barriers to recognize the most important barrier category and ranking of specific barriers within the categories to the development of smart cities in India. Through the existing literature, this work explored 31 barriers to smart cities development and divided them into six categories. This research work employed the fuzzy Analytic Hierarchy Process (AHP) technique to prioritize the selected barriers. Findings reveal that ‘Governance’ is documented as the most significant category of barriers to smart city development followed by ‘Economic; ‘Technology’; ‘Social’; ‘Environmental’ and ‘Legal and Ethical’. In this work, author also performed sensitivity analysis to show how robust is the findings of study. This research is useful to the government and policymakers for eradicating the potential interferences in smart city development initiatives in developing country like India.